2021
DOI: 10.1099/acmi.0.000236
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance profiles and genetic basis of resistance among non-fastidious Gram-negative bacteria recovered from ready-to-eat foods in Kibera informal housing in Nairobi, Kenya

Abstract: Objective. This cross-sectional study conducted in Kibera, Kenya, sought to gain insights on relative microbial contamination levels of popular unprocessed food types, determine antimicrobial resistance (AMR) burden and the carriage of integrons that are essential elements for spreading antimicrobial resistance genes (ARG). Foods analysed consisted of cooked vegetables (kale, cabbage, and nightshades), boiled cereal foods (beans, rice, and Githeri, which is a mixture of beans and maize), meat, Omena fish (frie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…More recently, Musila et al (2021) identified K. pneumoniae isolates with the bla OXA-181 carbapenemase gene. In addition, K. pneumoniae resistance to aminoglycosides, tetracyclines, chloramphenicol, and fluoroquinolones has also been observed in Kenya, typically associated with ESBL production in MDR [ 6 , 10 , 18 ]. Aminoglycosides are widely used to treat bacterial infections due to the ease of administration and access in Kenya [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Musila et al (2021) identified K. pneumoniae isolates with the bla OXA-181 carbapenemase gene. In addition, K. pneumoniae resistance to aminoglycosides, tetracyclines, chloramphenicol, and fluoroquinolones has also been observed in Kenya, typically associated with ESBL production in MDR [ 6 , 10 , 18 ]. Aminoglycosides are widely used to treat bacterial infections due to the ease of administration and access in Kenya [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aminoglycosides are widely used to treat bacterial infections due to the ease of administration and access in Kenya [ 19 ]. Musila et al (2021) also reported the 16S rRNA methyltransferase genes, rmtF and rmtC , in K. pneumoniae isolates which confer pan-aminoglycoside resistance [ 18 ]. Resistance to chloramphenicol and sulfonamides is high in part due to its use as a first-line treatment option for enteric infections such as typhoid and HIV prophylaxis in Kenya [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In each quadrant, proportionate sampling based on the number of fish products vendors in each cluster was done to get the number of participants. Random tables were used to randomly identify the participants, while the convenient sampling strategy described by Maina et al [ 15 ] was used to randomly sample the fish and fish products in the selected fish retail markets in the county. These markets included Kerugoya, Ndia, Kianyaga, Mwea, Sagana, and Tebere.…”
Section: Methodsmentioning
confidence: 99%
“…For library preparation, the extracted DNA was end-repaired using the NEBNext® UltraII End Repair/dA-Tailing kit using the manufacturer's instructions. LSK 109 ligation kit, EXP-NBD 104 (1-12), and EXP-NBD 114 (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) Native Barcoding kits were used to barcode each DNA sample and adapters added. The DNA library was loaded onto a FLO-MIN106 R9.…”
Section: Dna Extraction and Sequencingmentioning
confidence: 99%
“…In addition, KP resistance to aminoglycosides, tetracyclines, chloramphenicol, and fluoroquinolones has also been observed in Kenya, typically associated with ESBL-production in MDR (6,10). Aminoglycosides are widely used to treat bacterial infections due to the ease of administration and access in Kenya (18). Musila et al (2021) also reported the 16S rRNA methyltransferase genes, rmtF, and rmtC, in KP isolates which confer pan-aminoglycoside resistance.…”
Section: Introductionmentioning
confidence: 99%